Mathematical Literacy Ability Based on Higher Level Thinking - Meilynda Rizky Rianti; Toheri Toheri; Hadi Kusmanto (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
This The 21st century requires human resources who have superior quality with critical thinking skills, creativity, collaboration, and communication skills. Education is the main sector that plays a role in increasing the number of human resources with superior skills. The research objectives are: 1) Knowing the mathematical literacy skills of students 2) Knowing the higher order thinking skills of students 3) Knowing the correlation between mathematical literacy and students' higher-order thinking skills. The research method used in this research is correlational, without giving any treatment. The data collection technique in this study was a test technique, with the research population being students of class X SMA Negeri 2 Kuningan with a total of 249 students. The sampling technique used was Stratified Random Sampling so that the number of samples taken was 35 students. The results obtained that the level of mathematical literacy ability seen in each indicator obtained results on the formulate indicator with a mean value of 66.09 being in the good category, the mean value of the employing indicator of 78.43 being in the good category, while the mean value of the employing indicator was 78.43. the indicator interprets the mean value of 27.51 in the low category. Meanwhile, the level of students' higher order thinking skills seen in each indicator obtained an average score or mean from the analyzing indicator (C4) of 56, the C5 indicator evaluated getting the mean or average value of 53.57, and the mean value of the C6 indicator. create 44.57. The mean or average value obtained for each indicator is interpreted based on test scores with a sufficient category for the C4 indicator, the low category for the C5 indicator, and the very low category on the C6 indicator, and the results of this study indicate that there is a significant correlation between mathematical literacy and ability students' higher order thinking. Keywords: mathematical literacy, high order thinking skill.